(untitled) (Ustozlar uchun, 2026)
Color terminology reflects the way cultures conceptualize reality. Although humans share similar biological perception of color, the linguistic naming, symbolic meaning, and cultural interpretation of colors vary across nations. This article analyzes the linguistic nature of color terms and examines their national characteristics through the works of major scholars such as Berlin & Kay, Lakoff, Wierzbicka, and cultural linguists.